2023
DOI: 10.3389/fneur.2023.1102353
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Optic Neuritis Network (ACON): Study protocol of a non-interventional prospective multicenter study on diagnosis and treatment of acute optic neuritis

Abstract: Optic neuritis (ON) often occurs at the presentation of multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), and myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD). The recommended treatment of high-dose corticosteroids for ON is based on a North American study population, which did not address treatment timing or antibody serostatus. The Acute Optic Neuritis Network (ACON) presents a global, prospective, observational study protocol primarily designed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Our exploratory study suggests that there is no benefit to structural or visual outcomes when adding oral prednisone taper to IVMP in patients with acute CIS-and MS-related ON. We are currently enrolling patients in a larger prospective study to validate our results using LC-BCVA, VEP, MRI and OCT with the aim to prevent unnecessary steroid use and related side effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our exploratory study suggests that there is no benefit to structural or visual outcomes when adding oral prednisone taper to IVMP in patients with acute CIS-and MS-related ON. We are currently enrolling patients in a larger prospective study to validate our results using LC-BCVA, VEP, MRI and OCT with the aim to prevent unnecessary steroid use and related side effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuritis, a demyelinating inflammation of the optic nerve, affects 3–5 people per 100,000 people annually worldwide ( 1 ). The Optic Neuritis Treatment Trial (ONTT) found that most patients with optic neuritis in the study had a connection with multiple sclerosis (MS).…”
Section: Introductionmentioning
confidence: 99%